PENGARUH KARAKTER WIRAUSAHA PADA MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA JURUSAN PENDIDIKAN EKONOMI DI STKIP BIMA - Hartoyo Hartoyo; Wahyuni Wahyuni (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2020)
The purpose of this study was to determine the effect of entrepreneur charasters in entrepreneurship courses learning on entrepreneurial interest in students of the Department of Economic Education at STKIP Bima. The hypothesis that the researchers propose in this study is that there is an influence of entrepreneurship courses on entrepreneurial interest in students of the Department of Economic Education at STKIP Bima.Data collection methods in this study used a questionnaire (questionnaire) and documentation. Researchers used questionnaires to obtain data on entrepreneurship courses and entrepreneurship interests. While the data analysis technique used to obtain instrument validity is the Pearson product moment formula and to obtain the reliability of the instrument, namely the Cronbach alpha formula. Meanwhile, to find out whether or not there is an influence of teacher teaching skills on student interest in learning using the Pearson Product Moment formula which then tests its hypothesis with the t test.Based on data processing, the value of tcount is 2.32258 and ttable at the significance level of 5% with df = n - 2 = 38 - 2 = 37 which is 2.028094. Thus the price of t is greater than table which is 2.32258> 2.028094. So it can be concluded that the alternative hypothesis (Ha) is accepted, this shows that there is an influence of entrepreneurship courses affecting the interest of entrepreneurship in students majoring in Economic Education at STKIP Bima